Occurrence, Clinical Presentation of Amphistomosis Affected Dairy Cattle in the Cauvery Delta Region of Tamil Nadu - M. Venkatesan; A. Latchumikanthan; M.K. Vijayasarathi; K. Jayalakshmi; M.Saravanan; M. Veeraselvam; P. Selvaraj (The Indian Veterinary Journal, 2025)
The present study included a total of 128cross-bredJersey cows presented to the Veterinary Clinical Complex, Veterinary College and Research Institute, Orathanadu, Thanjavur district of Tamil Nadu with a history of jowl edema and voiding foul-smelling diarrhea during the period January to December 2020.Breed-wise distribution of paramphistomosis infestation was higher in Jersey crossbred (59.37%) followed by Holstein Friesian Crossbred (25%), non-descript breed (10.93%) and Kangayam (4.68%). Older aged dairy cows (>4 years, 28.3%), were found to have a higher infection with paramphistomosis. On clinical examination, increased / normal body temperature, heart, respiratory rate, slight pale to congested conjunctival mucous membranes, and jowledema were noticed in the animals. Microscopic examination of fecal samples of animals and micrometry confirmed that 151 x 72 μmsize oval-shaped eggs with distinct operculum as amphistome eggs. The animals were treated with Oxyclozanide@ 18.7mg/kg body weight orally for 2 days subsequently along with supportivetherapy, improvements were noticed in the health status of the animals after treatment. Further examination of fecal samples from these animals did not show any ova of endoparasites on the 1515th day after treatment. This study describes the occurrence and management of Paramphistomosis in cattle from the Cauvery Deltaregion of Tamil Nadu.